The Association of Autoantibodies in Hyperthyroid Heart Disease Combined with Pulmonary Hypertension - Xiujuan Zhang; Lin Chen; Jianping Sheng; Chaoying Li; Yong He; WenXia Han (International Journal of Endocrinology)
Hyperthyroidism is a clinical state that results from increased thyroid hormone levels which has a significant impact on cardiac function and structure. Graves’ disease is the most common cause of hyperthyroidism in iodine-replete areas. Hyperthyroid heart disease may be associated with pulmonary hypertension in patients who have overt hyperthyroidism. To investigate the association of pulmonary hypertension induced by hyperthyroid heart disease and autoantibody, one hundred and one cases with hyperthyroid heart disease who were consecutively admitted to the inpatient department of endocrinology and metabolism of the Shandong Provincial Hospital between November 2014 and April 2018 were collected and analyzed statistically. According to the Independent samples T-test, variance analysis, chi-square test, Pearson linear correlation analysis, and logistic regression, there was a good correlation between pulmonary artery systolic pressure and thyroid stimulating hormone (TSH) and receptor antibodies (TRAb) (r = 0.264, P=0.025) (OR = 1.037, P=0.029), but there was no significant correlation between the pulmonary artery systolic pressure and other thyroid-related parameters (FT3, FT4, TSH, anti-TPO, and anti-TG). Based on variance analysis, PASP rose as the level of TRAb gets higher. What is more, patients with HHD combined with PH showed a significantly higher serum level of TRAb; moreover, serum TRAb concentration was remarkably correlated with the PASP level. Therefore, TRAb participates in the process of pulmonary hypertension caused by hyperthyroid heart disease.